Intervención socioeducativa como eje de coordinación interdisciplinar en el Grado Educación Social. Análisis de una experiencia APS. - Herrera-Pastor, David; Alcalá-del-Olmo-Fernández, María José; Santos-Villalba, María Jesús; Giménez-Gualdo, Ana María (Octaedro, 2024)
Service Learning (SL) is a teaching methodology that combines learning and service in a real situation. Given its contribution to the process of acquiring professional skills, this study analyses the innovative nature of an ApS experience carried out in the second year of the Bachelor’s Degree in Social Education at the University of Malaga. This initiative was developed within the framework of a teaching improvement and coordination project involving four subjects. In this project, the students carried out the diagnosis, design, implementation and evaluation of a socio-educational intervention process in contexts of psychosocial risk. Around 60 students participated in the experience. Each group of 4-6 students materialised these actions in a third sector entity that developed socio-educational programmes with children, young people and families. The evaluation of the experience was carried out using a mixed methodology, based on an ad hoc questionnaire. The results indicated the achievement of the objectives and a positive evaluation by the students, showing the innovative characteristics of the experience. In conclusion, it is noted that with this innovation and coordination project between subjects, an experiential learning experience was achieved that empowered socio-educational intervention, enhancing an adequate professional performance adjusted to the real needs of the socio-educational context.
Se adjunta la publicación y la recepción de correo de la editorial con el Visto Bueno para su inclusión y difusión en RIUMA con los derechos de autor.
Keywords: Enseñanza - Innovaciones; Educación - Aspectos sociales; Investigación activa en educación; Aprendizaje-Servicio; Educación superior; Educación social; Coordinación interdisciplinar; Intervención socioeducativa